(untitled) (Environment & Health, 2022)
Objective: We determined the diagnostic value of indicators of the content of C-reactive protein and proteinogram as the markers of systemic inflammation in workers of the mining and metallurgical industries with pneumoconiosis in combination with COPD in the system of measures aimed at timely diagnosis, treatment and prevention of this occupational lung pathology. Results: It has been established that in workers of the mining and metallurgical industry with pneumoconiosis in combination with COPD, the content of C-reactive protein is significantly increased, which is a predictor of the activation of the organism’s immune system, the occurrence of nonspecific reactions to prolonged bronchopulmonary inflammation with the formation of a predisposition to infectious complications.The revealed changes determine an unfavourable prognosis for further stimulation of the hyperproduction of pro-inflammatory triggers. The total protein content in the combination of pneumoconiosis and COPD corresponds to the physiological constants. The increase in the albumin content is a consequence of the chronicity of bronchopulmonary inflammation and a sign of the formation of dehydration processes of the organism of sick workers. A decrease in the content of the fraction of alpha-1-globulins, an increase in the content of the fraction of alpha-2-globulins is a sign of the imbalance of protein metabolism, and an increase in the content of beta-globulins (in absolute numbers) and a slight decrease in the content of gamma globulins are a sign of "compensation" for the exchange of large molecular globulin fractions. Thus, the study of the content of C-reactive protein and protein fractions in the peripheral blood among workers of the mining and metallurgical industry with pneumoconiosis in combination with COPD is an important link in assessing the activity of systemic inflammation within the framework of measures aimed at timely diagnosis, treatment, and prevention of this occupational diseases of lungs. Conclusions: Among the workers of mining and metallurgical industries with pneumoconiosis in combination with COPD, the high content of C-reactive protein causes significant activity of systemic inflammation with the stimulation of its mediators, determining a negative prognosis for development of the disease. The content of C-reactive protein in workers with pneumoconiosis stipulates a significant pro-inflammatory potential of this disease and allows you to consider it as an important sign of the reaction of the lymphoid system of lungs to the formation of coniotic changes and a tendency to damage the bronchial mucosa. The absence of significant differences in the indicators of the content of total protein and its fractions in sick workers is a sign of "compensation" of their metabolism during prolonged bronchopulmonary inflammation.